1974
DOI: 10.1002/ajpa.1330410214
|View full text |Cite
|
Sign up to set email alerts
|

Genetic studies in Paraguay: Blood group, red cell, and serum genetic patterns of the Guayaki and Ayore Indians, Mennonite settlers, and seven other Indian tribes of the Paraguayan chaco

Abstract: Genetic studies of 540 Paraguayan Indians from nine tribal groups and 51 Mennonites are presented for ABO, MNSs, P1, Rh, Kell, Lewis, Duffy, Diego; for serum immunoglobulins and haptoglobins, G6PD‐deficiency, and thalassemia trait. Group O gene frequencies for all Indian groups were 1.00; for r (cde), 0.00. Tapiete, Lengua, Toba, and Sanapana Rz (CDE) frequencies were among the highest ever reported. N frequencies were high for Ache Kwera (Guayaki), Lengua, Cheroti, Guarayu, Tapiete; N and s low for Ayore. MS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
1

Year Published

1977
1977
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 24 publications
2
11
1
Order By: Relevance
“…As was indicated in the footnote of Table 2, for these and other blood group markers we adopted the frequencies reported by Cabutti and Palatnik (1973), which derive from the same group of researchers to which four of us belong (A.S.G., F.R.C., C.D., and S.A.A.). The frequency for L ‫ء‬ MS among the Toba given here (16%) is similar to those found in three other series (18 -30%; Matson et al, 1968Matson et al, , 1969Pagés Larraya et al, 1978), but much lower than that observed by Brown et al (1974), at 58%, for members of this tribe. In relation to FY ‫ء‬ A, our figure (55%) is similar to those found in two other studies (45-59%; Matson et al, 1968;Brown et al, 1974), but different from the 100% prevalence found by Matson et al (1969) in another Toba population from Salta.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…As was indicated in the footnote of Table 2, for these and other blood group markers we adopted the frequencies reported by Cabutti and Palatnik (1973), which derive from the same group of researchers to which four of us belong (A.S.G., F.R.C., C.D., and S.A.A.). The frequency for L ‫ء‬ MS among the Toba given here (16%) is similar to those found in three other series (18 -30%; Matson et al, 1968Matson et al, , 1969Pagés Larraya et al, 1978), but much lower than that observed by Brown et al (1974), at 58%, for members of this tribe. In relation to FY ‫ء‬ A, our figure (55%) is similar to those found in two other studies (45-59%; Matson et al, 1968;Brown et al, 1974), but different from the 100% prevalence found by Matson et al (1969) in another Toba population from Salta.…”
Section: Resultssupporting
confidence: 89%
“…Pagés Larraya et al (1978) found a very low P ‫ء‬ 1 frequency in this group (9%), while Brown et al (1974) obtained a higher value (62%) than that observed by Quilici (1975) (42%) or here (53%), if our typings are combined with those of Matson et al (1969), which show a similar prevalence. For FY ‫ء‬ A, the result by Brown et al (1974) was similar (67%) to the one obtained here (62%), but both differed from the 100% value obtained by Matson et al (1969) for this allele. The differences among series, in the two sets, are statisticaly highly significant (P, 2 ϭ 81.0; 4 d.f.…”
Section: Resultscontrasting
confidence: 44%
See 1 more Smart Citation
“…Dornelles et al (2004), using the same Ayoreo sample set as Salzano et al (1988), found the Ayoreo to have unusual blood group, protein, and mtDNA HVI profiles relative to other South American population samples (although their Alu insertion-based analysis did not show any atypical results). Researchers proposed various explanations, including a unique origin of the Ayoreo (Métraux, 1946), local group endogamy, and female infanticide (Brown et al, 1974;Bugos, 1985;Pérez Diez and Salzano, 1978).…”
Section: Discussionmentioning
confidence: 98%
“…While other researchers proposed an east-west continental division in patterns of genetic variation (e.g., Fuselli et al By many accounts, the Gran Chaco region represents a distinct environmental landscape that contributed to a unique human social and cultural landscape in South America (Métraux, 1946;Miller, 1999). The idea that the Gran Chaco also exhibits a distinct human biological landscape with respect to other South American populations is more recent, asserted first through blood and protein studies (Brown et al, 1974; Goicoechea et al, 2001a,b;Matson et al, 1969), anthropometric studies (Marcellino and Colantonio, 1999), and most recently, through molecular studies (Demarchi and Mitchell, 2004;Demarchi et al, 2001;Dornelles et al, 2004;Goicoechea et al, 2001b).In particular, Demarchi et al (2001) provided evidence in support of biological distinctiveness using mitochondrial DNA (mtDNA) haplogroup-based lineages of peoples inhabiting the central part of the Gran Chaco region, or Central Chaco. They found that populations in the Central Chaco seem to be the most genetically diverse and least genetically differentiated of any in South America.…”
mentioning
confidence: 99%